Acute Cellular Rejection: Is It Still Relevant? - Koutsokera, Angela; Levy, Liran; Pal, Prodipto; Orchanian-Cheff, Ani; Martinu, Tereza (Seminars in Respiratory and Critical Care Medicine, 2018)
Despite significant progress in the field of transplant immunology, acute cellular rejection (ACR) remains a very frequent complication after lung transplantation (LTx), with almost 30% of LTx recipients experiencing at least one episode of treated ACR during the first year of follow-up. Most episodes respond to the first-line immunosuppressive treatment and are rarely a direct cause of death. However, the association of ACR with later adverse outcomes, such as chronic lung allograft dysfunction, bronchial stricture, and infectious complications associated with the intensification of immunosuppression, negatively impacts long-term survival. The burden imposed on patients and health-care resources is even higher in cases of refractory or recurrent ACR, which accelerates lung function decline. Although important laboratory and clinical research conducted over the last two decades has improved our understanding of the mechanisms underlying ACR, there are still many uncertainties about the risk factors for ACR, the optimal monitoring strategies, and the prediction of long-term outcomes. These knowledge gaps contribute to the large variability in clinical practice among LTx centers, which renders multicenter studies of ACR challenging. In this review, we summarize current evidence on the epidemiology, pathogenesis, and risk factors of ACR. We describe diagnostic and therapeutic approaches that are currently used in the clinical practice and also review promising diagnostic tools that are under investigation. Associations between ACR and other adverse outcomes of LTx are examined. Finally, within each topic of discussion, we highlight the main areas of controversy and opportunities for future research.
Keywords: lung transplantation; acute rejection; cellular rejection; transplant immunology